1996
DOI: 10.1074/jbc.271.31.18892
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Family of Streptococcal Surface Proteins with Extremely Repetitive Structure

Abstract: The group B Streptococcus (GBS) causes the majority of life-threatening bacterial infections in newborn children. Most GBS strains isolated from such infections express a surface protein, designated Rib, that confers protective immunity and therefore is of interest for analysis of pathogenetic mechanisms. Sequence analysis demonstrated that Rib has an exceptionally long signal peptide (55 amino acid residues) and 12 repeats (79 amino acid residues each) that account for >80% of the sequence of the mature prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
160
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 120 publications
(166 citation statements)
references
References 22 publications
6
160
0
Order By: Relevance
“…The N-terminal regions of Alps share 60 -100% similarity at the amino acid level (Fig. 3), suggesting that they may function similarly (17,23,37,39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The N-terminal regions of Alps share 60 -100% similarity at the amino acid level (Fig. 3), suggesting that they may function similarly (17,23,37,39).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the first methionine of the recombinant proteins is numbered Met 39 , as the first residue of the alpha C protein 2 N-terminal domain in the GenBank TM data base is Ser 52 .…”
Section: Methodsmentioning
confidence: 99%
“…The existence of a protein family was suggested by the observation that the Rib protein, purified from a type III GBS strain, is a homolog of the alpha C protein gene. It has a similar N-terminal encoding region, a series of 12 237-bp identical tandem repeats, and a highly conserved C-terminal encoding region (10). Phenotypic characteristics of alpha-like proteins from type V and VIII GBS suggest that these proteins also are related (4,5,11) and likely possess a similar genetic organization.…”
mentioning
confidence: 99%
“…Molecular characterization of the R28 protein [24] showed that it is a member of a family of extremely repetitive surface proteins first identified in the group B streptococcus (GBS; Streptococcus agalactiae) [26], which is often found in the normal vaginal flora and causes serious invasive disease in newborns [27]. The protein family that includes R28 was first defined by the GBS proteins Rib and α [26,28,29] and among these GBS proteins R28 is most closely related to Rib (Fig.…”
Section: Puerperal Fever and The R28 Proteinmentioning
confidence: 99%
“…The protein family that includes R28 was first defined by the GBS proteins Rib and α [26,28,29] and among these GBS proteins R28 is most closely related to Rib (Fig. 2).…”
Section: Puerperal Fever and The R28 Proteinmentioning
confidence: 99%